2013
DOI: 10.1007/s00405-013-2471-7
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and clinical characteristics of prelaryngeal lymph node metastasis in papillary thyroid cancer

Abstract: There is little data that determine the clinical characteristics of prelaryngeal lymph nodes (PLN) metastasis in patients with papillary thyroid cancer (PTC). The aims of this prospective study were to evaluate the incidence and the clinical characteristics of metastasis to the PLN for PTC patients who underwent total thyroidectomy and prophylactic central neck dissection. Sixty-seven patients who underwent total thyroidectomy and prophylactic bilateral central lymph node neck dissection for PTC were enrolled.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 12 publications
4
35
0
1
Order By: Relevance
“…Several reports have shown a significant association between Delphian lymph node metastasis and LNM. 22,23 When the Delphian lymph node is involved, the rate of LNM has been reported to range from 23.1% to 74%. 24,25 In our study, 18.1% of patients with ULNM and 36.2% of those with BLNM had Delphian lymph node metastasis.…”
Section: Neck Metastases Of Thyroid Cancer E499mentioning
confidence: 99%
“…Several reports have shown a significant association between Delphian lymph node metastasis and LNM. 22,23 When the Delphian lymph node is involved, the rate of LNM has been reported to range from 23.1% to 74%. 24,25 In our study, 18.1% of patients with ULNM and 36.2% of those with BLNM had Delphian lymph node metastasis.…”
Section: Neck Metastases Of Thyroid Cancer E499mentioning
confidence: 99%
“…First, this is a cross-sectional study without followup, which makes it impossible to determine whether DLN is a direct prognostic factor for unilateral PTC patients. [17][18][19][20][21][22][23]. The rst published study evaluating the associations between DLN metastasis and prognosis of thyroid cancer found that DLN metastasis was signi cantly associated with larger tumor size and was highly predictive of metastasis in other lymph nodes [17].…”
Section: Discusssionmentioning
confidence: 99%
“…The status of DLN metastasis has been shown to be important in deciding the extent of operation, estimating prognosis after the operation and planning radiotherapy [16]. However, there is no consensus on the value of DLN metastasis in the management of thyroid cancer and the number of studies evaluating the role of DLN metastasis in the prognosis of unilateral PTC is still very limited [17][18][19][20][21][22][23]. Therefore, the present study was designed to determine whether DLN metastasis is associated with any prognostic factors of unilateral PTC.…”
Section: Introductionmentioning
confidence: 99%
“…The manuscript published in this volume of the European Archives of Otolaryngology discusses the incidence and impact of pre-laryngeal nodal metastasis in thyroid cancer [1]. The authors have used the title pre-laryngeal synonymous to Delphian nodes.…”
mentioning
confidence: 99%